2007
DOI: 10.1063/1.2732443
|View full text |Cite
|
Sign up to set email alerts
|

The effect of size on the quantitative estimation of defect depth in steel structures using lock-in thermography

Abstract: An investigation into the effect of size on the quantitative estimation of defect depth in a steel specimen has been undertaken using lock-in thermography. Phase contrast measurements over circular defects of varying diameter and depth are presented for a range of excitation frequencies. It was found that the diameter of a defect had an appreciable effect on the observed phase angle which consequently has significant implications with regard to estimating defect depth. Phase contrast measurements for a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 32 publications
2
51
1
Order By: Relevance
“…7) due to a matched combination of depth-diameter-modulation frequency, resulting in little or no phase response (blind frequency [28]). Pickering and Almond [14] and Wallbrink et al [30] already observed the same effect for flat-bottomed artificial defects back-drilled in carbon fibre composite and steel plates, respectively, and concluded that blind frequency occurrence is related to the defect diameter/thermal diffusion length ratio. In our study we found that it also depends on the depth of the defect and appears for p/l* ratios higher than 0.30.…”
Section: Amplitude and Phase Angle Thermal Imagesmentioning
confidence: 79%
“…7) due to a matched combination of depth-diameter-modulation frequency, resulting in little or no phase response (blind frequency [28]). Pickering and Almond [14] and Wallbrink et al [30] already observed the same effect for flat-bottomed artificial defects back-drilled in carbon fibre composite and steel plates, respectively, and concluded that blind frequency occurrence is related to the defect diameter/thermal diffusion length ratio. In our study we found that it also depends on the depth of the defect and appears for p/l* ratios higher than 0.30.…”
Section: Amplitude and Phase Angle Thermal Imagesmentioning
confidence: 79%
“…The phase and amplitude information calculated by processing of recorded thermal images for each of the pixels are stored in the form of 2D matrices and subsequently converted to images known as phase image and amplitude image. [26][27][28][29] The amplitude image displays total temperature increase on the system during power cycling and phase image represents the time delay between powering a device and subsequent heating on the surface. Amplitude images are quantitatively analyzed to acquire the defect shape & size and phase image for defect's depth.…”
Section: Introductionmentioning
confidence: 99%
“…The online-mode requires special software that performs the necessary calculations during runtime (section 3.2 in [3]). Alternatively, special signal electronics can be used if a phase-locked temperature signal is available during runtime [4]. Data evaluation at the end of the measurement is usually realized offline by a Fast Fourier Transformation (FFT) or Discrete Fourier Transformation of multiples of an oscillation period (section 2.2 in [3].…”
Section: Introductionmentioning
confidence: 99%